(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Internet technology serves as a means of communication, business, health, learning and interaction and is equipped with various interesting features that cause users to linger in front of a computer or gadget. Excessive internet use has an impact, especially on mental health conditions. People with young age such as students have a more emotional relationship with social media, feel anxious when they cannot be online, have difficulty relaxing at bedtime for fear of missing out if there is a message. The purpose of the study was to identify the level of internet addiction in college students. This research method uses a quantitative descriptive research method design. Data collection using a questionnaire. Data analysis using univariate analysis. The results showed that of the 68 respondents, most respondents (60.3%) experienced mild internet addiction and a small proportion of respondents (19.11%) experienced moderate internet addiction. The conclusion of this study is that the level of internet addiction in nursing students is at a mild-moderate level.